Knowledge Bases Created for Discovering Business Opportunities: Empirical Results from Polish Enterprises - Krystian PAWLOWSKI (Communications of International Proceedings, 2025)
Purpose - Business knowledge bases are created for the purpose of preparing decisions at different levels of management: strategic, tactical and operational. The key area of interest in this article are strategic knowledge bases created for the discovery and creation of business opportunities (opportunities are a specific conjunction of chances, company potential and business goals). An important research goal in this article is to search for the answer to the question: whether and to what extent companies create such bases, and how they use them. Methodology/approach -These questions are a part of a wider research project on Industry 4.0 and business opportunity theory, conducted at the Faculty of Engineering Management, Poznan University of Technology. The 2024-25 survey was conducted in Poland, covering 300 industrial enterprises in 19 industries, including 60 large enterprises and 240 medium-sized enterprises. The respondents were board members and managing directors of companies and were invited to respond on a 1–5 (Likert) scale. Furthermore, the data was partially processed using the Spearman's rank correlation test (Statistica 13.3). Findings - The results of the survey indicated that there is a correlation between increased availability of data and information and contribute to accelerating entry into new sectors, new domestic markets and new foreign markets.
Keywords: knowledge management; knowledge base; opportunity; opportunity discovery; opportunity management